Narrative Techniques in Contemporary Social Prose - Alifah, Nur (Journal of Literary Prose and Society, 2024)
This research explores the narrative techniques employed in contemporary social prose to reflect and critique societal norms and expectations within specific cultural contexts. By examining works from a range of modern authors, this study identifies and analyses narrative strategies such as unreliable narration, stream of consciousness, fragmented structure, and shifting perspectives. These techniques are increasingly used to highlight social issues, challenge conventional values, and deepen readers' understanding of diverse cultural experiences. Through close readings of selected texts, this paper investigates how these narrative devices enable authors to subtly subvert or directly question prevailing ideologies, offering alternative viewpoints and fostering empathy. This research also considers the impact of regional influences on narrative choices, examining how distinct cultural and social elements shape storytelling methods and thematic focus. By shedding light on these narrative approaches, this study contributes to an understanding of how contemporary social prose functions as a dynamic space for cultural critique and dialogue, reflecting the complexities of modern society.